2016
DOI: 10.1177/1059712316664120
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive behaviors in multi-agent source localization using passive sensing

Abstract: In this paper, the role of adaptive group cohesion in a cooperative multi-agent source localization problem is investigated. A distributed source localization algorithm is presented for a homogeneous team of simple agents. An agent uses a single sensor to sense the gradient and two sensors to sense its neighbors. The algorithm is a set of individualistic and social behaviors where the individualistic behavior is as simple as an agent keeping its previous heading and is not self-sufficient in localizing the sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…In addition, their aim is more toward achieving single source localization rather than gradient following. Shaukat and Chitre (2016) presents an underwater application with autonomous robots to localize an RF beacon. Robots employ a method that eventually results in adaptive group coherence, depending on proximity to the source.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, their aim is more toward achieving single source localization rather than gradient following. Shaukat and Chitre (2016) presents an underwater application with autonomous robots to localize an RF beacon. Robots employ a method that eventually results in adaptive group coherence, depending on proximity to the source.…”
Section: Related Workmentioning
confidence: 99%
“…Several previous theoretical models of collective motion have found that adaptable interactions, i.e., interactions that can change according to the local environment, can improve the cohesiveness and performance of swarms [21][22][23] . Accordingly, in light of our experimental results, we sought to study the effect of the individual's ability to change its walking properties.…”
Section: Sociality-dependent Pwmentioning
confidence: 99%
“…Recently, coordination control for multiagent systems (MASs) has received enormous attention due to its widespread applications, such as marine environment monitoring [1], multiships cooperative combat [2], and source localization [3,4]. Depending on the different theories, these coordination control problems are mainly classified into three types: consensus [5][6][7], flocking [8][9][10], and formation control [11,12].…”
Section: Introductionmentioning
confidence: 99%